2002
DOI: 10.1191/0267659102pf610oa
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiopulmonary bypass management on postcardiac surgery renal function

Abstract: Our data suggest that current clinical CPB management impacts postoperative renal function. We found that patients with normal preoperative renal function who developed postoperative ARF had longer CPB duration, lower CPB perfusion flow, and longer periods on CPB at pressures < 60 mmHg compared to patients with no post CPB ARF. However, our data do not allow us to separate these CPB-related factors from the potential influence of perioperative low cardiac output syndrome as a cause for postoperative ARF. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 24 publications
7
87
0
7
Order By: Relevance
“…Current data is insufficient to confirm the association between these CPB parameters and the risk of CSA-AKI [2,71] . Other more established CPB-related risk factors are duration of CPB (> 100-120 min), perfu- Najafi M. Creatinine, AKI and cardiac surgery outcome sion pressure, hemodilution during CPB, blood transfusion, hemolysis, most commonly due to cardiotomy suction, and embolism [2,95,96] . The role of CPB in inducing systemic inflammatory response syndrome (SIRS) and consequently CSA-AKI has been shown in different cardiac surgery events.…”
Section: Intraoperative Risk Factorsmentioning
confidence: 99%
“…Current data is insufficient to confirm the association between these CPB parameters and the risk of CSA-AKI [2,71] . Other more established CPB-related risk factors are duration of CPB (> 100-120 min), perfu- Najafi M. Creatinine, AKI and cardiac surgery outcome sion pressure, hemodilution during CPB, blood transfusion, hemolysis, most commonly due to cardiotomy suction, and embolism [2,95,96] . The role of CPB in inducing systemic inflammatory response syndrome (SIRS) and consequently CSA-AKI has been shown in different cardiac surgery events.…”
Section: Intraoperative Risk Factorsmentioning
confidence: 99%
“…[24] Furthermore, the more time MAP is below 50mmHg or 60mmHg during CPB, the more likely is for acute renal injury (AKI) to arise. [25,26] Kanji and colleagues also found that a drop in MAP bigger than 26mmHg during CPB compared to pre-bypass MAP was associated with AKI. [27] Blood Flow versus Blood Pressure: "Pros and Cons"…”
Section: Blood Pressure During Cpb: Role and Particularitiesmentioning
confidence: 97%
“…KBP süresi arttıkça ve KBP sıra-sında 60 mmHg altındaki düşük perfüzyon basıncı ile bu düşük perfüzyon periyotlarının uzunluğu postoperatif böbrek yetmezliği görülme insidansının artmasında en önemli faktör olarak kabul edilmektedir (5) . Hipotermi, nonpulsatil sirkulasyon, düşük kardiyak output sendromu ile kanamaya bağlı hipotansiyon ve hipovolemiye bağlı perfüzyon bozuklukları gibi nedenler özellikle renal transplant hastalarında infeksiyon ve greft rejeksiyon riskini arttırmaktadır (7) .…”
Section: Marfan Sendromu (Mfs)unclassified
“…Preoperatif dönemde normal böbrek fonksiyonuna sahip hastalarda bile postoperatif dönemde % 4 ile 7.7 oranında böbrek yetmezliği gelişebilmektedir. Hipotermi ve hipovolemiye bağlı düşük perfüzyon basıncı ile pulsatil olmayan kan akımı postoperatif böbrek yetmezliğinin en önemli faktörleri olarak kabul edilmektedir (5,6) . Aynı nedenlerle renal transplantasyon yapılmış hastalarda allogreft böbreğin enfeksiyon, disfonksiyon ve greft rejeksiyon riski daha da yüksektir (7) .…”
Section: Introductionunclassified